Implementing the PAINRelieveIt Randomized Controlled Trial in Hospice Care: Mechanisms for Success and Meeting PCORI Methodology Standards. (July 2017) - Ezenwa, Miriam O.; Suarez, Marie L.; Carrasco, Jesus D.; Hipp, Theresa; Gill, Anayza; Miller, Jacob; Shea, Robert; Shuey, David; Zhao, Zhongsheng; Angulo, Veronica; McCurry, Timothy; Martin, Joanna; et al.
This purpose of this article is to describe how we adhere to the Patient-Centered Outcomes Research Institute's (PCORI) methodology standards relevant to the design and implementation of our PCORI-funded study, the PAIN Relieve It Trial. We present details of the PAIN Relieve It Trial organized by the PCORI methodology standards and components that are relevant to our study. The PAIN Relieve It Trial adheres to four PCORI standards and 21 subsumed components. The four standards include standards for formulating research questions, standards associated with patient centeredness, standards for data integrity and rigorous analyses, and standards for preventing and handling missing data. In the past 24 months, we screened 2, 837 cancer patients and their caregivers; 874 dyads were eligible; 223.5 dyads consented and provided baseline data. Only 55 patients were lost to follow-up—a 25% attrition rate. The design and implementation of the PAIN Relieve It Trial adhered to PCORI's methodology standards for research rigor.